2001
DOI: 10.1046/j.1365-2044.2001.01787.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of moderate hypovolaemia on microcirculation in healthy older blood donors

Abstract: SummaryCompensation for acute blood loss requires cardiovascular integrity. In older people, asymptomatic cardiovascular impairment is common. In these subjects, even moderate blood loss is often treated by external volume replacement although its benefits are not clear. We investigated the effect of 450 ml of blood loss on the microcirculation and compensatory mechanisms in healthy older blood donors. Red blood cell count, plasma viscosity and protein concentration were measured. Plasma volume replacement was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 16 publications
3
27
0
1
Order By: Relevance
“…Another potential weakness with this population was that we collected blood at the end of a routine blood donor session. Hemodilution develops gradually and can be expected to change hemoglobin values by ϳ5%, and less in those with a high hematocrit (43 ). We observed the same pattern in relation to age and sex when we adjusted for hematocrit or excluded individuals with low hematocrits.…”
Section: Discussionsupporting
confidence: 60%
“…Another potential weakness with this population was that we collected blood at the end of a routine blood donor session. Hemodilution develops gradually and can be expected to change hemoglobin values by ϳ5%, and less in those with a high hematocrit (43 ). We observed the same pattern in relation to age and sex when we adjusted for hematocrit or excluded individuals with low hematocrits.…”
Section: Discussionsupporting
confidence: 60%
“…The activation of humoral systems and the shift of fluid from an extravascular compartment to the blood also dampen these changes during longer bleedings [1,22]. However, a recent study showed fluid replacement occurs rapidly, within the time range of the present study i. e. 6-7 min [12]. Alltogether, these compensatory mechanisms explain why a 10 % blood volume reduction does not markedly affect BP [5,9,28,32].…”
Section: Discussionmentioning
confidence: 48%
“…During a normative donation of 400 ml of whole blood, about 10% of the total blood volume is taken from the human circulation within several minutes, Most blood donors generally can tolerate a blood loss of such magnitude even in the elderly (Gandini et al 1999;Janetzko et al 1998Janetzko et al , 2001, however, about 0.15% of donors experience severe adverse reaction such as syncope, with loss of consciousness due to decreased cerebral perfusion. Many studies (Vespa et al 1997(Vespa et al , 2005Janetzko et al 2001;Zöllei et al 2004;Pestel et al 2006;Pestel et al 2010) regarding physiological responses to hemorrhage have been performed in a variety of species and with many different approaches. Zöllei et al (2004) studied autonomic responses to blood donation in 48 healthy volunteers and concluded that the 350-400 ml acute volume loss in 5 min lead to sympathetic activation, which was followed by increased systolic, diastolic and mean blood pressure.…”
Section: Introductionmentioning
confidence: 99%